PENGAJARAN DAN PELATIHAN AKUNTANSI KAPITALISASI BUNGA DI SMA RICCI 1 JAKARTA BARAT - Chelsya (Jurnal Serina Abdimas, 2025)
The procurement of fixed assets constructed with funding from long-term loans is crucial for companies. From long-term loans, there is loan interest that can be capitalized into fixed assets. The application of interest capitalization accounting must follow applicable financial accounting standards (SAK). According to PSAK 26 of 2018, all long-term loans used to fund the development of fixed assets (construction of fixed assets) can be recorded as fixed assets. Borrowing costs related to the construction or production of fixed assets can be capitalized as the cost of acquiring fixed assets (specific debt), while other borrowing costs must be recognized as expenses (general debt). The calculation of loan costs that can be capitalized on fixed assets uses the average method for calculating the percentage interest rate on other loans (general debt) and calculating the average carrying amount of expenditure (average fixed asset construction expenses). The calculation of the interest percentage rate on other loans is calculated by dividing the total interest cost by the total other loans. The calculation of the average expenditure for the construction of fixed assets financed from other loans (general debt) multiplied by the capitalization period. The PKM activities of interest capitalization accounting teaching and training aim to develop the understanding and knowledge of Ricci 1 High School students. PKM will be held on April 28, 2025, at 09.00-12.00 face-to-face. The methods used in PKM activities are teaching, training, and discussion methods. The target output of the achievement is proceedings, HKI, and products in the form of posters. ABSTRAK Pengadaan aset tetap yang dikonstruksi dengan pendanaan dari pinjaman jangka panjang sangatlah krusial bagi perusahaan. Dari pinjaman jangka panjang, terdapat bunga pinjaman yang dapat dikapitalisasi menjadi aset tetap. Penerapan akuntansi kapitalisasi bunga harus mengikuti standar akuntansi keuangan yang berlaku (SAK). Menurut PSAK 26 Tahun 2018, semua pinjaman jangka panjang yang digunakan untuk mendanai pembangunan aset tetap (konstruksi aset tetap) dapat dicatat sebagai aset tetap. Biaya pinjaman yang berkaitan dengan konstruksi atau produksi aset tetap dapat dikapitalisasi sebagai biaya perolehan aset tetap (specific debt), sementara biaya pinjaman lainnya harus diakui sebagai beban (general debt). Perhitungan biaya pinjaman yang dapat dikapitalisasi ke aset tetap menggunakan metode average untuk perhitungan tarif persentase bunga dari pinjaman lainnya (general debt) dan menghitung average carrying amount of expenditure (rata-rata pengeluaran konstruksi aset tetap). Perhitungan tarif persentase bunga dari pinjaman lainnya dihitung dengan membagi total biaya bunga dengan total pinjaman lainnya. Perhitungan rata-rata pengeluaran untuk konstruksi aset tetap yang dibiayai dari pinjaman lainnya (general debt) dikalikan dengan periode kapitalisasi. Kegiatan PKM pengajaran dan pelatihan akuntansi kapitalisasi bunga bertujuan untuk mengembangkan pemahaman dan pengetahuan siswa-siswa SMA Ricci 1. PKM diadakan tanggal 28 April 2025, pada jam 09.00-12.00 secara tatap muka. Metode yang digunakan dalam kegiatan PKM adalah metode pengajaran, pelatihan, dan diskusi. Target luaran capaian adalah prosiding, HKI, dan produk berupa poster